2022
DOI: 10.1111/1759-7714.14642
|View full text |Cite
|
Sign up to set email alerts
|

The risk and prognostic factors for liver metastases in esophageal cancer patients: A large‐cohort based study

Abstract: Background: This retrospective study aimed to explore risk factors for liver metastases (LiM) in patients with esophageal cancer (EC) and to identify prognostic factors in patients initially diagnosed with LiM. Methods: A total of 28 654 EC patients were retrieved from the Surveillance, Epidemiology and End Results (SEER) database from 2010 to 2018. A multivariate logistic regression model was utilized to identify risk factors for LiM. A Cox regression model was used to identify prognostic factors for patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…Additionally, liver metastasis can result in complications such as liver failure, jaundice, and ascites, significantly affecting a patient’s quality of life and contributing to disease severity. Our study’s results align with Luo’s findings, in which the presence of liver metastasis led to shorter survival [ 45 ]. In the liver metastasis group, individuals with upper esophageal cancer had the worst survival rates, followed by those with middle- and lower-segment involvement [ 46 ].…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, liver metastasis can result in complications such as liver failure, jaundice, and ascites, significantly affecting a patient’s quality of life and contributing to disease severity. Our study’s results align with Luo’s findings, in which the presence of liver metastasis led to shorter survival [ 45 ]. In the liver metastasis group, individuals with upper esophageal cancer had the worst survival rates, followed by those with middle- and lower-segment involvement [ 46 ].…”
Section: Discussionsupporting
confidence: 91%
“…There were two studies which suggested that the presence of liver metastases was an unfavorable prognostic factor in patients with esophageal cancer including both squamous cell carcinoma and adenocarcinoma 21,22 . A large cohort‐based study demonstrated that esophageal cancer patients with liver metastases had shortened OS compared with those without liver metastases (6.00 months vs. 15.00 months) 21 . In another cohort of patients with stage IV esophageal cancer from the Surveillance, Epidemiology, and End Results (SEER) database, liver metastasis was identified as one of the independent risk factors for early death (defined as death within 3 months of diagnosis) 22 .…”
Section: Discussionmentioning
confidence: 99%
“… 21 , 22 A large cohort‐based study demonstrated that esophageal cancer patients with liver metastases had shortened OS compared with those without liver metastases (6.00 months vs. 15.00 months). 21 In another cohort of patients with stage IV esophageal cancer from the Surveillance, Epidemiology, and End Results (SEER) database, liver metastasis was identified as one of the independent risk factors for early death (defined as death within 3 months of diagnosis). 22 Of note, these previous studies were performed before immune checkpoint inhibitors were used in advanced esophageal cancer patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, liver metastasis in esophageal cancer engenders a substantial impact on patient prognosis. Not only does it signal advanced-stage disease, but it also portends a poor prognosis, resulting in metabolic disorders due to liver dysfunction, circulatory problems stemming from liver failure, pain, weight loss, and the potential development of multiple organ dysfunction syndrome (MODS) in the advanced stages 25 .…”
Section: Introductionmentioning
confidence: 99%